PENINGKATAN KEMAMPUAN LANSIA DALAM PENGELOLAAN KESEHATAN PADA MASA KLIMAKTERIUM MELALUI EDUKASI DAN PENDAMPINGAN DI MAJELIS PENGAJIAN ‘AISYIYAH AL KAHFI BANTUL - Diniyah, Kharisah; Wahyuhidaya, Pratika; Kristiana, Dita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Increased life expectancy has implications for the growing number of elderly people, including women entering menopause. Lack of knowledge about the physical and psychological changes during this period can cause anxiety, reduce quality of life, and hinder independence in meeting basic needs. This community service activity was carried out at the 'Aisyiyah Al Kahfi Jotawang Bangunharjo Sewon Bantul Islamic Study Group to improve the ability of the elderly to manage their health during menopause. The methods used included counseling, health screening, and training in preventive measures through exercise for the elderly. The results showed an increase in participants' knowledge, openness in discussing health issues, and independence in carrying out simple preventive measures. The attendance rate reached 90-95% with high enthusiasm. This program had an impact on increasing the congregation's awareness and concern for health. In the future, activities can be expanded to include early detection of cervical cancer for women of reproductive age